Manifestations of Othman bin Foduye ‘s influence on Mohammed bin Abd al-Karim al-Mughaili (Sultanic Literature as a model) - fatha, Mohamed; chabani, Noureddine (The Algerian Historical Journal, 2026)
This article deals with the manifestations of Sheikh Osman bin Foduye the Nigerian influenced by the Algerian Imam Mohamed bin Abd al-Karim al-Mughili of Tlemcen on the field of "The Science of Sultanic Literature," by reviewing the foundations and methodology of this science in both worlds and then tracking its emergence in the Hausa region of northern Nigeria; It is linked to the journey of Al-Mughaili to the great Sahara and the Western Sudan, as well as to the factors contributing to his development , particularly the thought of Al-Mughaili through his letters and writings to the kings and princes of the Western Sudan. It also attempts to extract the manifestations of Sheikh Osman ibn Foduye’s affectionate and Mughaili based on Maliki doctrine , whether during his reign on Sokoto state founded by himself at the begining of the (19 century /13 AH), or by his over 100 works. The study also highlights an important aspect of the role played by Middle Maghreb scholars in cultural communication; It was between the Central Maghreb country (Algeria) and its neighbouring territories, particularly the Sudan.